Profile Digitalization of Ahlul Irfan Islamic Boarding School through the Development of a WordPress-Based Website: Digitalisasi Profil Pesantren Ahlul Irfan melalui Pengembangan Website Berbasis Wordpress - Fajar Tridian Syaputra; Daffa Alifio Ardyananda; Taufikurrahman; Atma Putra Wicaksana; Faizal Muhammad Maldini Ffirda (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
The Ahlul Irfan Islamic Boarding School lacks an effective digital platform. Through the Community Service Program (KKN), students from UPN "Veteran" East Java developed a WordPress-based website to publish the school's profile and information. The implementation method included needs analysis, design, implementation, and management training. The website features the school's profile, programs, and news, supporting digital transformation and information dissemination. This activity aims to increase the school's visibility in the digital era and strengthen communication with the community. This program also serves as a model for implementing digitalization for similar educational institutions. The development is expected to facilitate access to information for prospective students and the wider community. Furthermore, this website provides a foundation for technology management for the boarding school's administrators so they can adapt to digital developments.